Frequency of vitamin D deficiency among teenagers of a Moscow sample - E. E. Mihailov; T A Korotkova; N V Demin; L I Benevolenskaya (Научно-практическая ревматология, 2005)
Objective. To study frequency of vitamin D deficiency among teenagers of a Moscow sample and its possible influence on bone mineral density (BMD) value. Material and methods. 318 teenagers (139 male, 179 female) aged 14 to 18 years were included. Clinical examination, anthropometry, calculation of daily calcium consumption, densitometry, 25(OH)D serum level, total and ionized calcium level evaluation were performed. Results. Boys consumed more calcium with milky products than girls (p<0,0001). Boys also had significantly higher concentration of total calcium (p<0,02) and 25(OH)D (p<0,0001). Frequency of vitamin D deficiency in girls was 10 times higher than among boys and came to 53,6%. Frequency of vitamin D hypovitaminosis and insufficiency was significantly higher among girls examined in February-March and frequency of vitamin D deficiency significantly prevailed in group examined in November- December (58,8%, p<0,0001). Correlation between serum concentration of 25(OH)D and age, height, weight, body mass index, daily calcium consumption, total and ionized calcium levels, BMD were not found. Girls with vitamin D deficiency aged 14-15 years showed increase of BMD in proximal femur.